ANALISIS FAKTOR KEJADIAN STUNTING ANAK USIA 0-59 BULAN DI INDONESIA (RISKESDAS 2007) - Jus’at, Idrus (Jurnal Nutrire Diaita (Ilmu Gizi), 2011)
AbstractRISKESDAS 2007 shows that the prevalence of stunting in 17 provinces, Indonesia for children under five year above the national prevalence. The aim of this study was to find out the relationship status of region, age, sex, residence, education of patriarch and household expenditure per capita per month in boys and girls aged 0-59 months in Indonesia, with stunting. We used secondary data from RISKESDAS 2007. The data includes are; 1)Independent Variables such as region, gender, age, residence, education of patriarch, and household expenditure per capita per month; 2)Dependent Variable is nutritional status (TB/U). The results shows that most of respondens are men 51.3% and female 48.7%. Sumatera Island and East Region in Indonesia more likely suffered stunting than Jawa-Bali Island (OR=1.117; OR=1.085; p<0,05), the man more likely suffered stunting than woman (OR=1.061; p<0,05), the group age> 5m (24-35)m high risk suffered stunting than the group age≤ 5m (OR=1.716; p<0.05), the rural area more likely suffered stunting than urban area (OR=1.323; p<0,05), people who has education < SLTP more likely suffered stunting than ≥ SLTP (OR=1.308; p<0,05), people who has in the middle low income (<5 quintile) more likely sufferd stunting than middle up income (≥5 quintile) (OR=1.512; p<0,05). The government should give more attention and supplementary feeding (PMT) for the group in age ≥5m.Keywords: stunting,under five year, age 0-59m